Pinpointing Defects in Grounding Grids with Multistatic Radars - Rodrigo M. S. de Oliveira; Pedro G. B. Maia (Energies)
In this paper, we propose a method for locating discontinuities in grounding grids using a multistatic radar. The objective is to determine the fault position in the structure by injecting an ultra-wideband pulse (Gaussian monocycle) at one of the corners of the grid and analyzing the transient signals obtained at two sensors and at the transceiver. To perform the analysis and validation of the developed method, simulations based on the finite-difference time-domain (FDTD) technique were carried out to numerically solve Maxwell’s equations. The voltage signals obtained in an intact grounding grid are used as a reference. Differences between these reference voltages and the voltages obtained with the faulty grid are calculated. With these difference signals, the parameters of the radar ellipses and circle are obtained, which delimit the area where the fault can be found. These parameters depend on the wave propagation speed and the arrival times of the signals at the sensors and the transceiver. The results show that the proposed method is able to reduce the estimated fault location area to a range of 2% to 19% of the total grid area. In addition, the average distance between the actual fault and the center of the estimated region varies between 3.0 and 4.0 m.